Non-Affirmative Curriculum Theory in a Cosmopolitan Era? - Michael Uljens (Universidade Federal de Sergipe, 2016)
National curriculum making and curriculum theory are challenged by globally growing political, economic and technological interdependencies, transnational homogenization and aggregation processes. In addition increasing pluralisms within nation states present new topics to be solved. These issues are not new from an education theory perspective. A task and contribution in modern education has been a concept explaining how e.g. socialization (social cohesion) and personalization (individuation) may be considered as integrated rather than excluding processes. The modern, or classic, approach early identified dilemmas connected to a reproduction- and transformation oriented curricula, as well as dilemmas emanating from descriptive-technological and normative theory. This article elaborates on relational core concepts developed in nineteenth century modern education theory (Fichte, Hegel, Schleiermacher, Herbart, Snellman). Utilizing concepts from modern education theory a non-affirmative position is argued for as an answer to parts of contemporary challenges.